Climatic change, habitat modification and relative age of dung beetle taxa (Coleoptera: Scarabaeidae, Hydrophilidae, Histeridae, Staphylinidae) in the South-Western Cape - Davis, Adrian Louis Victor (Department of Biological Sciences, 2014)
Bibliography: leaves v. 1, 156-171.